The People’s Poet: A Marxist Reading of Pablo Neruda - Jagdalla, Marieta (International Journal of Psychosocial Rehabilitation, 2021)
Chilean poet, Pablo Neruda was known chiefly for his bold poetical imagery and his very flippant political affinities. However, a fact that is irrefutable is that the bard was a communist to the core. Choosing to work for his people and to live with them as one of them, the Nobel laureate gathered adequate experiences to form his own Philosophy of Life. His poems speak of pain, loss, shock, betrayal and a tumultuous history of political stake-placing. The poet took to writing not only to express himself and his soul, but also to escape the horrors of the path leading to a large dream, however momentarily. The very eventful journey of a loveless child into the hearts of millions of people, through his recklessly charming way with words, is a mystery to one and all. The approaches adopted to make extensive studies of Neruda’s psyche, his ideological bearings, and his impromptu choices in life, too, have yielded little. The Marxist ideological influence upon the poet, however, remains unchallenged and clear as day. Neruda wrote not just as a proletariat, but also lent his voice to those who seemed to have surrendered theirs to one higher. The absolute unattainability of unity, togetherness and universality of brotherhood among the Americas was what kept the poet unrelenting in his path. This paper proposes to invite attention to the role of Marxism in the making of a poet who learnt to love not just his people, but also his earth, his air, his water and his fire. Neruda’s portrayal of power dynamics, sexuality and fraternity, in his poetry, will be analyzed here through a Marxist reading of his work. The paper also employs a Biographical Approach of study for a better understanding of what made the poet bleed.